A ferroelectric relaxor polymer-enhanced p-type WSe2 transistor. Issue 4 (8th January 2018) - Yin, Chong; Wang, Xudong; Chen, Yan; Li, Dan; Lin, Tie; Sun, Shuo; Shen, Hong; Du, Piyi; Sun, Jinglan; Meng, Xiangjian; Chu, Junhao; Wong, Hon Fai; et al.
Abstract : A novel high-performance few-layer WSe2 p-FETs doped and gated by the ferroelectric relaxor tripolymer P(VDF-TrFE-CFE). Abstract : WSe2 has attracted extensive attention for p-FETs due to its air stability and high mobility. However, the Fermi level of WSe2 is close to the middle of the band gap, which will induce a high contact resistance with metals and thus limit the field effect mobility. In this case, a high work voltage is always required to achieve a large ON/OFF ratio. Herein, a stable WSe2 p-doping technique of coating using a ferroelectric relaxor polymer P(VDF-TrFE-CFE) is proposed. Unlike other doping methods, P(VDF-TrFE-CFE) not only can modify the Fermi level of WSe2 but can also act as a high- k gate dielectric in an FET. Dramatic enhancement of the field effect hole mobility from 27 to 170 cm 2 V −1 s −1 on a six-layer WSe2 FET has been achieved. Moreover, an FET device based on bilayer WSe2 with P(VDF-TrFE-CFE) as the top gate dielectric is fabricated, which exhibits high p-type performance over a low top gate voltage range. Furthermore, low-temperature experiments reveal the influence of the phase transition of P(VDF-TrFE-CFE) on the channel carrier density and mobility. With a decrease in temperature, field effect hole mobility increases and approaches up to 900 cm 2 V −1 s −1 at 200 K. The combination of the p-doping and gating with P(VDF-TrFE-CFE) provides a promising solution for obtaining high-performance p-FET with 2D semiconductors.